PENDAMPINGAN PENGELOLAAN SISTEM AKUNTANSI UNTUK PENINGKATAN INFORMASI KEUANGAN PADA TRIPEL 8 CAR WASH MALANG - Lituhayu, Anagata Salsabila; Melinda, Debby; Wachyudi, Stefanny; Junaidi, Thitania Chatrine; Pratama, Bagas Brian; Anugrah, Audito Aji; Oktariani, Fitri; Cahyadi, Rino Tam (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2024)
This community service activity was carried out against the backdrop of the importance of good accounting management in supporting entrepreneurship, especially for small and medium enterprises such as Tripel 8 Car Wash in Malang. The purpose of this activity is to improve the understanding and skills of accounting management for the owners and employees of Tripel 8 Car Wash, so they can manage business finances more efficiently and accurately. The methods of implementing the activities include training and direct assistance conducted through joint discussions and consultation sessions. The results of the activity showed a significant increase in the ability of Tripel 8's owners to record financial transactions, prepare financial statements, and understand basic accounting and entrepreneurship concepts. Additionally, this assistance also demonstrated an increased awareness of the importance of good financial management in supporting business success. The conclusion from this activity is that accounting training and assistance can have a positive and tangible impact on financial management and entrepreneurial development in small and medium enterprises such as Tripel 8 Car Wash. This activity also reinforces the importance of good accounting management as a key factor in business success.